A practical approach to predicting cross-flow and in-line VIV response for deepwater risers. (August 2015) - Xue, Hongxiang; Wang, Kunpeng; Tang, Wenyong
Abstract: In this study, a practical model is proposed to predict cross-flow (CF) and in-line (IL) vortex-induced vibrations of a flexible riser in time domain. The hydrodynamic force as a function of non-dimensional amplitude and frequency is obtained from the forced vibration experimental data of a two-dimensional cylinder. An empirical nonlinear damping model is used to simulate the hydrodynamic damping outside the experiment's range. Coupling effect of CF and IL-VIV is taken into account by implanting a magnification model for the IL hydrodynamic force associated with CF amplitude, and by increasing the non-dimensional amplitude corresponding to the IL hydrodynamic coefficient in the second excitation region. The experimental models of flexible riser under the uniform and sheared current are simulated to validate the proposed model. The predicted displacement, curvatures, excited modes and fatigue damage show reasonable agreement with the measured data.